Results, Performance Budgeting and Trust in Government - Arizti, Pedro; Brumby, Jim; Manning, Nick; Senderowitsch, Roby; Thomas, Theo (World Bank, Washington, DC, 2017)
The book identifies four categories of performance budgeting, namely direct performance budgeting, performance informed budget (PIB), opportunistic performance budgeting and presentational performance budgeting. While the Conference papers often refer to performance budgeting broadly defined, much of the book focuses on PIB, the most common category of performance budgeting adopted to date, making the argument that this is likely to be the most applicable in many Latin American countries. The book combines two seemingly diverse governance topics, adopts contrasting analytic styles to address these, and seeks to draw out their inter-connections, with particular reference to Organization for Economic Co-operation and Development (OECD) and Latin American countries. The first topic is PIB, which is discussed largely from the practical perspective of policy makers and practitioners, reflecting that it is a major public administration reform that has been underway for several decades. The second topic is the trust of citizens and firms in government. This book is divided into seven chapters. Chapter one provides an overview of PIB, building on two decades of experience and lesson-learning, and sets out the key themes that provide the basis for the discussions in the subsequent chapters. Chapter two introduces the concept of trust in government, particularly in OECD and Latin American countries, and explores why this matters for development. Chapters three, four, and five explore key dimensions of PIB, including the institutional foundations, the production of performance information, and the uses of performance information. Chapter six considers the impact of performance improvement on trust in government in OECD and Latin American countries. Chapter seven provides a guide for practitioners on PIB.